On the magnetic aggregation of Fe3O4 nanoparticles. (January 2021) - Karvelas, E.G.; Lampropoulos, N.K.; Benos, L.T.; Karakasidis, T.; Sarris, I.E.
Highlights: In-vivo MRI-guided drug delivery concept bottleneck is the weak magnetic nanoparticles response A comprehensive study to estimate the mean length and time to aggregate is presented Several cases with nanoparticles having various diameters and concentrations are simulated as magnetic field increases. Mean length of aggregates scales linear with diameter and magnetic field, however, concentration increase results in a weaker effect. Mean time to aggregate is of the same order as in microparticles, although, with an opposite trend. Abstract: Background and objective In-vivo MRI-guided drug delivery concept is a personalized technique towards cancer treatment. A major bottleneck of this method, is the weak magnetic response of nanoparticles. A crucial improvement is the usage of paramagnetic nanoparticles aggregates since they can easier manipulated in human arteries than isolated particles. However its significance, not a comprehensive study to estimate the mean length and time to aggregate exists. Methods The present detailed numerical study includes all major discrete and continues forces and moments of the nanoscale in a global model. The effort is given in summarizing the effects of particle diameter and concentration, and magnetic field magnitude to comprehensive relations. Therefore, several cases with nanoparticles having various diameters and concentrations are simulated as magnetic field increases. Results It is found that aggregations with maximum length equal to 2000 nm can be formed. In addition, the increase of the concentration leads to a decrease in the amount of the isolated particles. Consequently, 33% of the particles are isolated for the concentration of 2.25 mg / ml while 13% for the concentration of 10 mg / ml . Moreover, the increase of the permanent magnetic field and diameter of particles gives rise to an asymptotic behavior in the number of isolated particles. Furthermore, the mean length of aggregates scales linear with diameter and magnetic field, however, concentration increase results in a weaker effect. The larger aggregation that is formed is composed by 21 particles. Smaller time is needed for the completion of the aggregation process with larger particles. Additionally, the increase of the magnitude of the magnetic field leads to a decrease in the aggregation time process. Therefore, 8.5 ms are needed for the completion of the aggregation process for particles of 100 nm at B 0 = 0.1 T while 7 ms at B 0 = 0.9 T . Surprisedly, the mean time to aggregate is of the same order as in microparticles, although, with an opposite trend. Conclusions In this study, the evolution of the mean length of aggregations as well as the completion time of the aggregation process in the nano and micro range is evaluated. The present results could be useful to improve the magnetic nanoparticles assisted drug delivery method in order to minimize the side effects from the convectional cancer treatments like radiation and chemotherapy.